Governmentality and Pedagogical Apparatuses in Management Times - Silvia M. Grinberg (Universidade de Lisboa, 2016)
Change and the novel have become privileged instances, images of obligation and of how things should be: schools must change and teachers must become instruments of transformation; rather than teach, they must guide learning processes. We understand that those faces of novelty ceaselessly express modes of confrontation and of struggle. In response to the hypotheses, increasingly fashionable in recent years, surrounding processes of deinstitutionalization and in direct relation to de-subjectivation, this work delves into how daily life at schools is enacted, shaped, affected from the perspective of governmentality studies. Through the notion of the pedagogical apparatuses, we evidence the heterogeneous, diffuse, contradictory, and overlapping ways that daily life operates in the government of population, that is, the experience of the State that involves both government processes as such (the direction of conduct) and ways to avoid being governed, that is, ways that we, as subjects, invent ourselves in the world. Thus, with Foucault, we can assert that things might have changed a little... the battles may not have the same face. Rather than deny institutions and declare their senselessness, we frame the question of pedagogy as a political question in relation to the new faces of current battles.